Canine distemper: an epidemiological, clinical, laboratory and therapeutic analysis in an endemic area of western Bahia (Research, Society and Development, 2022)
This study aimed to carry out an epidemiological, clinical, laboratory and therapeutic analysis of canine distemper in the municipality of Barra, western region of Bahia. To this end, a retrospective study was carried out through the survey of clinical records of the University Veterinary Hospital (HVU) of the Universidade Federal do Oeste da Bahia, including records with presumptive or confirmatory diagnoses. Data related to the animals (age, sex, race); sanitary management (vaccination), as well as data on the symptoms, diagnosis, treatment and outcome of the cases were collected. Of the 33 animals included in the present study, 63.63% had ophthalmic signs, 57.57% had at least one nervous sign and integumentary, digestive, respiratory and nonspecific signs were also reported. A total of 75.75% of the animals were considered domiciled, and only 15.15% of them had their vaccination for distemper up to date. Although 54.55% of the animals with distemper were up to 2 years old, no association between the disease and age, however, an association was found between mixed-breed animals and the presence of distemper (P = 0.025). Treatments were symptomatic, with the most frequently prescribed vitamin complexes (69.70%) and antimicrobials (63.64%). The outcome of the cases was retrieved from nine clinical records, and a statistical association was found between the completion of the prescribed treatment and the recovery of the animals (Fisher test, P = 0.027). That said, educational policies aimed at animal health should be instituted, aiming at the expansion of prophylactic methods for distemper through systemic vaccination protocols.